1991
DOI: 10.1073/pnas.88.24.11182
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the discontinuous binding site in human interleukin 1 beta for the type I interleukin 1 receptor.

Abstract: Human interleukin 113 (IL-113) exerts its diverse biological effects by binding to specific receptors on target cells. Two ypes of IL-1 receptor (IL-1R) have been identified: the type I IL-1R (p80) and the type II IL-1R (p68). Using site-specific mutagenesis, we have identified the binding site on IL-11 for the murine type I IL-1R. Analogs of the IL-1fL protein containing defined amino acid substitutions were produced and tested for competitive binding to the two IL-1Rs. Substitutions of the amino acids at sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 42 publications
1
34
1
Order By: Relevance
“…Ferrets have several amino acids that, from the discontinuous binding site for the type I IL-1 receptor, maintain the conformation of IL-1β and have carboxyl-terminal endpoints for active protein (TDF) that are conserved in the same positions, as seen in previous reports [10,14,16,19,20]. In ferret IL-1β, comparison of each residue suggests that these conserved amino acids have the same function as those of human IL-1β.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Ferrets have several amino acids that, from the discontinuous binding site for the type I IL-1 receptor, maintain the conformation of IL-1β and have carboxyl-terminal endpoints for active protein (TDF) that are conserved in the same positions, as seen in previous reports [10,14,16,19,20]. In ferret IL-1β, comparison of each residue suggests that these conserved amino acids have the same function as those of human IL-1β.…”
Section: Discussionmentioning
confidence: 68%
“…These amino acids form a discontinuous binding site for the type I IL-1 receptor in humans [16]. These amino acids were conserved in ferret were found at the same positions in other mammals, except for the mouse (Fig.…”
Section: Characterization Of Mature Proteins Related To the Function mentioning
confidence: 80%
“…We thus turned to previously reported sitedirected mutation studies to investigate if any Lys, Pro, or Thr residues on IL-1b had been shown to be important or critical for receptor binding. Interestingly, Lys 209 of IL-1b was found to be absolutely essential for activity, with mutants showing ,1% of activity (37,38 , which is itself located on the third Ig-like C2 domain of IL-1RI. This loop on the receptor is rich in acidic residues; in particular, there are 3 Asp and 1 Glu residues in a continuous sequence (residues 251-254).…”
Section: Computer Modeling Suggests Binding Of Kdpt To the Il-1ri Antmentioning
confidence: 99%
“…Extensive mutagenesis studies of both IL-1␣ and IL-1␤ have identified the amino acid residues important for binding of these ligands to the Type I IL-1R (21)(22)(23)(24)(25)(26). In these studies, all of the residues involved in binding to the Type I IL-1R, although not contiguous, are located on one face of the IL-1 structure (the open end of the ␤-barrel).…”
mentioning
confidence: 99%